A study to determine various factors associated with high-risk pregnancies - Bhandari, Aditi; Rasania, S. K.; Verma, Savitri; Gupta, Kamna; Dangayach, Nidhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: All pregnancies are at risk even though most of the pregnancies and childbirth worldwide are uneventful. Early and regular prenatal care helps many women have healthy pregnancies and deliveries without complications. With this background, our study was planned to determine various factors associated childbirths with high-risk pregnancies among women attending ante natal care centre of Delhi. Methods: This was a cross-sectional, observational study conducted at the antenatal clinic of a primary health centre (PHC) during March-April 2023 in 50 high risk pregnancies. Details of pregnant women with a minimum of one high risk factor available were recorded. Results: Prevalence of adequate knowledge of government schemes and facilities plays a key role in determining the booking status of antenatal women. In our study, we found that 64% of the females presented to the ante natal clinic (ANC) in the first trimester of the pregnancy, 20% in the second trimester and 16% were in the third trimester at the time of their first visit. Severe anemia was present in 32% of the patients, while diabetes mellitus, hypertension and infectious diseases, each of which were found in 24% patients. Conclusions: With the increasing age of the female, advancing gestational age and lower socio-economic status, the number of risk factors present in a female tends to rise significantly. Therefore, a younger female from a higher socio-economic class presenting to the antenatal clinic in early stages of gestation would have a better pregnancy outcome due to lesser number of risk factors associated.